Three-dimensional relationships between condylar volume and dentoskeletal characteristics in Class II hyperdivergent female adults - Bingjie Xie; Lingyi Huang; Anna Feng; Xianglong Han; Ye Tian; Juan Li (BMC, 2023)
Abstract Background This study aimed to determine the differences among various volumes of condylar osseous patterns and the corresponding dentoskeletal characteristics based on the risk of temporomandibular disorder. Methods Craniofacial spiral computed tomography data of 60 Class II hyperdivergent female adults were divided into normal, resorptive, flattened, and osteophyte groups based on condylar osseous forms. The condylar volumes of each group were compared, and their correlations with the dentoskeletal characteristics were assessed in three dimensions. Pairwise least significant difference tests were used to examine individual pairwise differences between groups, and one-way analysis of variance was used to measure differences among multiple groups. Pearson correlation and Spearman rank correlation analyses were used to determine the correlation between condylar volume and dentofacial characteristics. Statistical significance was established at p < 0.05. Results The condylar volume in the normal group was significantly greater than that in the changed groups, with no significant differences between the subgroups. The decrease in condylar volume was associated with a retruded and clockwise-rotated mandible with shorter rami. Condylar volume was negatively correlated with overjet, the alveolar height of the lower anterior and posterior teeth, sagittal inclinations of the lower teeth, intermolar width of the mandibular first molars, and width between the corresponding alveolar crests. Conclusion Multiple three-dimensional dentoskeletal characteristics of Class II hyperdivergent female adults are correlated with condylar bony changes, regardless of the form. These results could be helpful in indicating potential pathological changes in the temporomandibular joint and in making proper treatment plans for these patients.